Does gender moderate the association between socioeconomic status and health? Results from an observational study in persons with spinal cord injury living in Morocco - Limacher, Regula; Hajjioui, Abderrazak; Fourtassi, Maryam; Fekete, Christine (Frontiers in Rehabilitation Sciences, 2023)
Background Socioeconomic status (SES) and gender are well-known social determinants of health. However, their impact on health in populations with physical disabilities in low-resource countries is still lacking. Therefore, the objective of this study was to investigate associations of individual SES with health and the moderating effect of gender on this association in a Moroccan population with a physical disability, namely spinal cord injury. Methods Cross-sectional survey data from 385 participants with spinal cord injury living in Morocco were analyzed. SES was operationalized by education level, household income, financial hardship, and subjective social status. Health indicators included secondary conditions, pain, vitality, quality of life, and general health. Associations between SES and health indicators were investigated using linear and logistic regressions. To test the potential moderation of gender, interaction terms between SES and gender were introduced in regression models. Results Financial hardship and lower subjective social status were associated with poorer health outcomes in four out of five indicators in the total sample. In contrast, education and income were inconsistently associated with health. Overall, gender did not moderate the association between SES and health, except that educational inequalities in general health were more pronounced in women, and the observation of a trend for a stronger negative effect of subjective social status on men's than woman's health (p > 0.05). Conclusion This study revealed that subjective indicators of SES negatively impact on health, whereas evidence for the moderating role of gender in this association was weak. These findings underline the importance to reduce social marginalization and poverty in populations with disabilities in low-resource countries to reduce their double burden of living with a disability and encountering social disadvantages through low SES.